The Role of Environment in English Language Learning Among Young Bracelet Sellers at Kuta Beach: an Analysis of Grammar Mastery - Muhammad Fahrurrozi; M. Adib Nazri; Hajriana Arfah; Laila Wati (Departement of Mathematics Education, 2024)
The study aims to assess the role of the Kuta Beach environment on the English language learning of young bracelet sellers there and how they use English in their daily activities. This study encourages qualitative approach, data collection techniques using, observation, interview and documentation. The researcher found and concluded that the environment at Kuta Beach plays a significant role in the development of English language skills among these children even to develop next level that is grammar mastery. Even they are not necessarily having access to informal education such as course. They are able to communicate effectively due to their regular interactions with tourists from diverse country. The lively and socially engaging environment of Kuta Beach provides them with opportunities to practice and improve their language skills.